DESIGN AND IMPLEMENTATION OF DATA ACQUISITION HARDWARE MODULE IN AUTOMATED MEASUREMENT SYSTEM FOR WHEEL DRIVE ELECTRONICS DEVELOPMENT - Robbani, Arba
Wheel drive electronics is Brushless Direct Current motor control module attached to reaction wheel that is used to control the attitude of the satellites. At the development stage, this module needs to be verified at the component level. However, with the many electronic system factors in this module, now it is still partially measured so that it will increase the testing time. For this reason, an automatic measurement system was developed. One part of it is the data acquisition hardware. This data acquisition is used to retrieve data from sensors, convert analog signals to digital, and send data to computers to store, manipulate, and display data. This data acquisition hardware mainly uses Arduino DUE based on Atmel SAM3x8E ARM Cortex M3 and ADS1256 as analog to digital converter with 24bits resolution. This device is modular and integrated. Modular means that it can be easily replaced and integrated consisting of various sensors that support the automatic measurement method. This device is also equipped with a relay for excess current flowing into this module. After that, the sensor data obtained will be sent to the computer to use a protocol that contains measured information, sensor data, and sampling time. These data can be used as comparison with wheel drive electronics and checks of wheel drive electronic systems such as stator current, motor speed, power consumption, temperature, and voltage, especially back-EMF. From the results, the stator current error is 4.6%, the BEMF voltage error is 0.1775%, the power consumption error is 4.61%, the temperature error is 0.5oC, and the motor speed resolution is ± 0.05 RPM.